Pengaruh Kepemilikan Manajerial dan Capital Intensity terhadap Tarif Pajak Efektif - Vivi Tandean (Universitas Kristen Krida Wacana, 2023)
This research is a quantitative research which aims to fnd out how the inﬂuence of manajerial ownership and capital intensity on eﬀective tax rate in coal mining sector listed on the Indonesia Stock Exchange for the period 2016-2020. This study uses secondary data and data analysis used panel data regression. The simultaneous test results show the results all of independent variable have a signifcant eﬀect on eﬀective tax rate. The results of panel data regression annalysis show that partially manajerial ownership have not eﬀect on eﬀective tax rate and for variables of capital intensity have a negative and signifcant eﬀect on tax aggressiveness. Keywords: manajerial ownership, capital intensity